FRICTIONAL ELECTRICITY AND TOOL MATERIALS WEAR - Anatoly A. Ryzhkin; Victoria E. Burlakova (Вестник Донского государственного технического университета, 2018)
Thomson spatial heat sources power is determined. It is shown that the heating spatial source helps reduce the total flow quantity entering the plate, and expand heat penetration. The volume cooling source in the tool material plate, conversely, removes an additional quantity of heat from the contact zone increasing the temperature gradient and reducing the heating zone.